2010
DOI: 10.1118/1.3447722
|View full text |Cite
|
Sign up to set email alerts
|

Design of iterative ROI transmission tomography reconstruction procedures and image quality analysis

Abstract: Inexpensive pilot reconstruction techniques (analytical algorithms, very-coarse-grid penalized likelihood) are practical choices in many common cases. However, they may yield background images altered by edge degradation or beam hardening, inducing projection inconsistency in the data used for ROI reconstruction. The ROI images thus have significant streak and speckle artifacts, which adversely affect the resolution-to-noise compromise. In these cases, edge-preserving penalized-likelihood methods on not-too-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…For each of these patches a different energy and resolution model could be defined. This is very similar to the region of interest reconstruction proposed by Hamelin et al 29,30 and Yu et al 31 In these papers, the approach was used to obtain a high resolution reconstruction in a small region of interest, in combination with a coarser (and faster) reconstruction of the surrounding background. Here, this approach was extended to implement a locally improved energy model and improved sampling of the detector elements.…”
Section: Discussionmentioning
confidence: 62%
“…For each of these patches a different energy and resolution model could be defined. This is very similar to the region of interest reconstruction proposed by Hamelin et al 29,30 and Yu et al 31 In these papers, the approach was used to obtain a high resolution reconstruction in a small region of interest, in combination with a coarser (and faster) reconstruction of the surrounding background. Here, this approach was extended to implement a locally improved energy model and improved sampling of the detector elements.…”
Section: Discussionmentioning
confidence: 62%
“…That kind of approach has already be shown to reduce memory usage and computation time significantly 7 but to increase image noise. 8 We showed that using our method also an image quality close to full FOV iterative reconstruction can be reached.…”
Section: Discussionmentioning
confidence: 89%
“…In the upcoming sections we will refer to this approach as method Z. Hamelin et al extended the ROI reconstruction using a coarse-grid penalized likelihood (PL) full FOV reconstruction for the background and a fine grid for the ROI. 6,8 They show that artefacts, like beam-hardening or streaking, in the analytical reconstruction used by method Z propagate to the later ROI reconstruction. Using a not-too-coarse image grid in combination with an edgepreserving PL reconstruction produced significantly better images than method Z.…”
Section: Introductionmentioning
confidence: 96%
“…An additional step consisting of smoothing of the reprojected coarse grid line integrals was found to yield reduced noise in the ROI reconstruction (Rashed et al 2007). However, artifacts attributable to edge degradation and beam-hardening artifacts in the initial FBP were found in the iteratively reconstructed ROI obtained using this general approach (Hamelin et al 2010). …”
Section: Introductionmentioning
confidence: 99%